The complexity of the grid wireless mobility model - Kantabutra S. (2014)
This paper describes a communication model in a grid for mobile wireless networks and shows how to optimally solve some decision problems related to the model. We show that User Communication Problem (UCP) and Source Reachability Problem (SRP) can be most efficiently solved in polynomial time. Asymptotically time-optimal algorithms for solving these problems are also presented. In contrast to the first two "easy" problems, the intractability of the third problem called the Access Point Location Problem (APLP) is also shown and discussed. © 2008 IEEE.